Actinomicose mandibular em ovino: relato de caso - Antunes, J.m.a.p [UNESP]; Almeida, A.c.s [UNESP]; Ribeiro, M.g [UNESP]; Amorim, R.l [UNESP]; Hussni, C.a [UNESP]; Listoni, F.j.p [UNESP]; Megid, Jane [UNESP] (Instituto Biológico, 2012)
The primary agent of actinomicosis/mandibular osteomyelitis is Actinomyces bovis that infects mainly bones of the oral cavity of cattle, resulting in economic losses due to weight loss caused by pain on chewing. The diagnosis is usually made by a good clinical examination, radiographic, bacterioscopy and microbiological culture. This report describes the case of a sheep that had localized increase of the jaw, where the material from the lesion was collected for microbiological and histopathological diagnosis. Osteomyelitis was demonstrated by radiography. Piogranuloma was observed at the histophatology. Bacterioscopy evidenced a Gram-positive, branched, filamentous and catalase negative agent. The main clinical findings and diagnoses confirmed the occurrence of unusual jaw infection by A. bovis in a sheep.

O agente primário da actinomicose/osteomielite mandibular é o Actinomyces bovis que infecta principalmente ossos da cavidade oral de bovinos, acarretando prejuízos econômicos devido a perda de peso ocasionada pela dor à mastigação. O diagnóstico é comumente realizado por um bom exame clínico, radiográfico, bacterioscopia e cultivo microbiológico. Neste relato é apresentado o caso de um ovino com aumento localizado de mandíbula. O exame radiográfico demonstrou osteomielite. Amostras da lesão foram coletadas para realização de exame microbiológico e histopatológico. A histopatologia evidenciou lesão piogranulomatosa e na bacterioscopia foi demonstrado um agente Gram-positivo ramificado, filamentoso e catalase negativo. Os achados clínicos associados aos resultados dos exames complementares confirmaram a ocorrência incomum de infecção mandibular por A. bovis em um ovino.
Jaw actinomycosis in a sheep: case report
Keywords: Actinomyces bovis; actinomicose; osteomielite mandibular; mandíbula nodular; Actinomyces bovis; actinomicosis; mandibular osteomyelitis; lumpy jaw